INTERVENSI KEPERAWATAN KECEMASAN PADA PASIEN PRE OPERASI: LITERATUR REVIEW - Chatarina Hatri Istiarini; Efriane Pali Osa; Maria Titin Inya Ede (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Nursing Interventions for Anxiety in Patients Preoperative: Literature ReviewBackground: one of the psychological effects of surgery is anxiety (Sutejo, 2018). Anxiety management can be done in pharmacology (doctors) or non-pharmacology (nurses). One of the preoperative anxiety nursing interventions was learned through the identification of various related studies / Integrated Literature Review (IRL). Thus the authors are interested in identifying "How Anxiety Nursing Interventions in Patients Pre Operative: Literature Review". Objective: identifying anxiety nursing interventions in preoperative patients. Methods: the study was conducted using the Literature Review method. The steps are: problem identification, literature search, data identification, data analysis and reporting. Literature search using Google Scholar and Garuda Portal with inclusion criteria, namely Indonesian language articles, full text, and discussing preoperative patient anxiety. Results: there are 7 journals that fit the inclusion criteria. Researchers divided into five pre-operative anxiety nursing interventions: one journal (14%) explained identification of anxiety levels, two journals (29%) about anxiety coping strategies, two journals (29%) about nonpharmacological interventions reduced anxiety levels, one journal ( 14%) about the regulation of emotional anxiety, and one journal (14%) about anxiety management. Conclusion: anxiety nursing interventions in preoperative patients with anxiety identification, coping strategies, nonpharmacological interventions (music therapy, lavender oil administration, Wack Wednesday, healing touch, and hand reflexology), emotional regulation, and anxiety management.